Investigation on Potential ESKAPE Surrogates for 222 and 254 nm Irradiation Experiments - Gierke, Anna-Maria; Hessling, Martin (Frontiers in Microbiology, 2022)
Background: Due to the increase of multi-drug resistant pathogens, it is important to investigate further antimicrobial options. In order not to have to work directly with pathogens, the investigation of possible surrogates is an important aspect. It is examined how suitable possible surrogate candidates for ESKAPE pathogens are for UVC applications. In addition, the inactivation sensitivities to 222 nm and 254 nm radiation are compared in relation. Methods: Non-pathogenic members (Enterococcus mundtii, Staphylococcus carnosus, Acinetobacter kookii, Pseudomonas fluorescens and Escherichia coli) of genera of ESKAPE strains were photoinactivated in PBS with irradiation wavelengths of 222 and 254 nm (no non-pathogenic Klebsiella was available). Log reduction doses were determined and compared to published photoinactivation results on ESKAPE pathogens. It was assumed that non-pathogenic bacteria could be designated as surrogates for one wavelength and one ESKAPE strain, if the doses were between the 25% and 75% quantiles of published log reduction dose of the corresponding pathogen. Results: For all non-pathogen relatives (except Acinetobacter kookii), higher average log reduction doses were required for irradiation at 222 nm than at 254 nm. Comparison by boxplot, revealed that five of eight determined log reduction doses of the possible surrogates were within the 25% and 75% quantiles of the data for ESKAPE pathogens. The measured log reduction dose for non-pathogenic E. coli was above the 75% quantile at 222 nm and the log reduction dose for S. carnosus was below the 25% quantile at 254 nm. Conclusion: For more than half of the studied cases, the examined ESKAPE relatives in this study can be aped as surrogates for ESKAPE pathogens. Because of lack of data, no clear statement could be made for E. faecalis at 222 nm and A. baumanniii at both wavelengths.